Activation of brainstem neurons by underwater diving in the rat - Panneton, W Michael (Frontiers in Physiology, 2012)
The mammalian diving response is a powerful autonomic adjustment to underwater submersion greatly affecting heart rate, arterial blood pressure and ventilation. The bradycardia is known to be mediated by the parasympathetic nervous system, arterial blood pressure is mediated via the sympathetic system and still other circuits mediate the respiratory changes. In the present study we investigate the cardiorespiratory responses and the brainstem neurons activated by voluntary diving of trained rats, and, compare them to control and swimming animals which did not dive. We show that the bradycardia and increase in arterial blood pressure induced by diving were significantly different that induced by swimming. Neuronal activation was calculated after immunohistochemical processing of brainstem sections for Fos protein. Labeled neurons were counted in the caudal pressor area, the medullary dorsal horn, subnuclei of the nucleus tractus solitarii, the nucleus raphe pallidus, the rostroventrolateral medulla, the A5 area, the nucleus locus coeruleus, the Kölliker-Fuse area and the external lateral and superior lateral subnuclei of the parabrachial nucleus. All these areas showed significant increases in Fos labeling when data from voluntary diving rats were compared to control rats and all but the commissural subnucleus of the nucleus tractus solitarii, A5 area, and raphe pallidus were different from swimming rats. These data provide a substrate for more precise experiments to determine the role of these nuclei in the reflex circuits driving the diving response.